POSITIVE SKILL CLUSTERING IN ROLE‐ASSIGNMENT MATCHING MODELS. (10th April 2022) - Anderson, Axel
Abstract: Kremer and Maskin (1996, NBER Working Paper) explore matching when production involves defined roles. Despite underlying Cobb–Douglas production functions, the induced maximum production function is not supermodular (SPM), and positive sorting does not arise. This article introduces and solves a general class of role‐assignment matching models with general SPM production functions. The unique equilibrium entails a novel blend of positive sorting in the large, and locally negative sorting that I call positive clustering. I show how the equilibrium matching changes as the production function changes. In a dynamic extension, sorting, mobility, and wage inequality positively covary with changes in production across matching markets.